2007
DOI: 10.1063/1.2787528
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and vibrational study of platinum(II) anticancer drugs: cis-diamminedichloroplatinum (II) as a case study

Abstract: A conformational and vibrational analysis of cisplatin ͓cis-diamminedichloro-platinum͑II͔͒ ͑cDDP͒ is reported. Several theory methods ͑from Hartree-Fock to Møller-Plesset and density functional theory͒ combined with different all-electron basis sets are evaluated, in view of determining the best suited strategy for accurately representing this molecule. This choice is based on the best compromise between accuracy and computational requirements. Different scaling models of the cDDP vibrational modes were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(118 citation statements)
references
References 43 publications
12
105
1
Order By: Relevance
“…These results were interpreted in the light of the full conformational analysis previously performed by the authors for cisplatin [21][22][23]25,26 and the purine bases adenine 28 and guanine, 27 as well as for the optimized structures presently obtained for reduced glutathione (Fig. 2), [cDDP-A 2 ] and [cDDP-G 2 ] (Fig.…”
Section: View Article Onlinementioning
confidence: 69%
See 2 more Smart Citations
“…These results were interpreted in the light of the full conformational analysis previously performed by the authors for cisplatin [21][22][23]25,26 and the purine bases adenine 28 and guanine, 27 as well as for the optimized structures presently obtained for reduced glutathione (Fig. 2), [cDDP-A 2 ] and [cDDP-G 2 ] (Fig.…”
Section: View Article Onlinementioning
confidence: 69%
“…Different scaling factors were applied to distinct frequency sets: adapted from Merrick and co-workers 53 for the organic moieties of the adducts (0.9513 and 0.9846 below and above 700 cm À1 , respectively); and the parameters developed by Amado et al 22 , d NPtN )). This was considered a valid approach since the vibrational transition energies of the adenine and guanine ligands are well separated from those involving the metal (i.e.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained along this work were related with a thorough conformational analysis of the newly synthesised metal-based agents (by Raman, IR and INS coupled to theoretical approaches) [18][19][20][21][22][23][24][34][35][36] and with biological assays for the evaluation of cytotoxicity performed alongside on the same systems -cell growth and viability inhibition, as well as anti-angiogenic and anti-metastatic abilities [14][15][16]27,[40][41][42][43]45 -allowing us to establish a reliable correlation between structural/ conformational features, cytotoxic activity and impact on cellular metabolism. This data, coupled to previous INS and EXAFS studies on drug-DNA adducts (carried out at ISIS and DLS 18,21,23,24 ), will pave the way for future work on other promising cisplatin-like anticancer agents (both Pt(II) and Pd(II)) which have been studied by the team in the last few years, as well as on distinct human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The vibrational spectra of cisplatin have been the object of several experimental studies,5, 6, 7 whereas its high‐resolution crystal structure has been reported only some years ago 8. Besides experimental studies, several investigations have focused on the theoretical prediction of its structure and vibrational frequencies 6, 7, 9, 10.…”
mentioning
confidence: 99%